Mikołaj Zebrzydowski 1553–1620 : szkic biograficzny - Graff, Tomasz; Wołyniec, Bartłomiej; Wróbel, Elżbieta Elena (2020)
MIKOŁAJ ZEBRZYDOWSKI (1553–1620): A BIOGRAPHICAL SKETCHThis book by Tomasz Graff, Bartłomiej Wołyniec, and Sister Elżbieta Elena Wróbel, CSFN, is the first attempt at presenting a complete biography of Mikołaj Zebrzydowski, a Voivode of Krakow and one of the most important Polish politicians of the late sixteenth and early seventeenth centuries. This devout Catholic was also a patron and founder of numerous works of piety, the largest of which is the so-called “Jerusalem Calvary;” i.e., the Bernardine abbey and complex of pathways near his ancestral town of Zebrzydowice. Until the present day, it is one of the most important shrines devoted to the Passion and to Mary in Poland. Mikołaj was also the founder of the city Zebrzydów, present-day Kalwaria Zebrzydowska, just outside the abbey. Polish history textbooks tend to present Zebrzydowski as the main collaborator of and later successor to Jan Zamoyski, Grand Chancellor and Great Hetman of the Crown, who contested the policies of King Sigismund III Vasa and above all initiated the civil war of 1606-1609, which is often called Zebrzydowski’s rebellion in reference to him. The debate on his stance during the rebellion divided his contemporaries; it is present in the historical literature and broadly understood culture, including works of literature, up until today.